Doping i suplementy stosowane w bydgoskich siłowniach = Doping and supplementation applied in Bydgoszcz gyms - Szark-Eckardt, Mirosława; Kowalczyk, Łukasz; Żukowska, Hanna; Łubkowska, Wioletta (Journal of Education, Health and Sport, 2015)
Szark-Eckardt Mirosława, Kowalczyk Łukasz, Żukowska Hanna, Łubkowska Wioletta. Doping i suplementy stosowane w bydgoskich siłowniach = Doping and supplementation applied in Bydgoszcz gyms. Journal of Education, Health and Sport. 2015;5(11):577-594. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35700 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A577-594 http://pbn.nauka.gov.pl/works/684798 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Szark-Eckardt Mirosława, Kowalczyk Łukasz, Żukowska Hanna, Łubkowska Wioletta. Doping i suplementy stosowane w bydgoskich siłowniach. Quality in Sport. 2015;1(2):26-42. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Mirosława Szark-Eckardt, Łukasz Kowalczyk, Hanna Żukowska Uniwersytet Kazimierza Wielkiego Wydział Kultury Fizycznej, Zdrowia i Turystyki Wioletta Łubkowska Uniwersytet Szczeciński, Wydział Kultury Fizycznej i Promocji Zdrowia Doping i suplementy stosowane w bydgoskich siłowniach Doping and supplementation applied in Bydgoszcz gyms Streszczenie Celem pracy jest określenie jakich środków dopingujących oraz jakich suplementów diety używają osoby ćwiczące na siłowniach w Bydgoszczy. Badania zostały przeprowadzone wśród osób trenujących na siłowniach w Bydgoszczy. Metodą, która została zastosowana był sondaż diagnostyczny. Na podstawie badań można stwierdzić, że sterydy anaboliczno-androgenne są najczęściej stosowanym środkiem dopingującym. Badania wykazały również, że znaczna część badanych stosuje kreatynę w celu poprawienia wyglądu sylwetki, co wpływa na jakość ich treningów. Prawie wszyscy ankietowani natomiast twierdzą, że suplementacja jest zjawiskiem powszechnie występującym. Słowa kluczowe: doping, suplementy, siłownia, Bydgoszcz. Abstract The aim of the study is to determine what kind of doping and what kind of supplements are in use by those exercising in gyms in Bydgoszcz. The study was conducted among people practicing in gyms in Bydgoszcz. Method that was used was a diagnostic survey. Based on research it can be concluded that the anabolic androgenic steroids are the most commonly used doping. It can be also conclude that a significant proportion of respondents is using creatine to improve the appearance of the figure, which affects the quality of training. Almost all respondents claim that supplementation is a phenomenon commonly occured. Key words: doping, supplements, gym, Bydgoszcz.